Challenges of dosimetry of ultra-short pulsed very high energy electron beams. (October 2017) - Subiel, Anna; Moskvin, Vadim; Welsh, Gregor H.; Cipiccia, Silvia; Reboredo, David; DesRosiers, Colleen; Jaroszynski, Dino A.
Highlights: VHEE beams have the potential of becoming an alternative modality in radiotherapy. There is a need to establish accurate and reliable dosimetry for VHEEs. Ultrashort nature of VHEE pulses makes dosimetry challenging. Femto- and picosecond VHEEs are high-dose-per-pulse beams. Ionization chambers exhibit high ion recombination when exposed to ultrashort VHEE beam. Abstract: Very high energy electrons (VHEE) in the range from 100 to 250 MeV have the potential of becoming an alternative modality in radiotherapy because of their improved dosimetric properties compared with 6–20 MV photons generated by clinical linear accelerators (LINACs). VHEE beams have characteristics unlike any other beams currently used for radiotherapy: femtosecond to picosecond duration electron bunches, which leads to very high dose per pulse, and energies that exceed that currently used in clinical applications. Dosimetry with conventional online detectors, such as ionization chambers or diodes, is a challenge due to non-negligible ion recombination effects taking place in the sensitive volumes of these detectors. FLUKA and Geant4 Monte Carlo (MC) codes have been employed to study the temporal and spectral evolution of ultrashort VHEE beams in a water phantom. These results are complemented by ion recombination measurements employing an IBA CC04 ionization chamber for a 165 MeV VHEE beam. For comparison, ion recombination has also been measured using the same chamber with a conventional 20 MeV electron beam. This work demonstrates that the IBA CC04 ionization chamber exhibits significant ion recombination and is therefore not suitable for dosimetry of ultrashort pulsed VHEE beams applying conventional correction factors. Further study is required to investigate the applicability of ion chambers in VHEE dosimetry.